2021
DOI: 10.22225/seas.5.2.4020.145-150
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Indigofera Leaf and Corn as Fermented Feed on the Growth of Arabic Chicken (Gallus turcicus)

Abstract: This study aims to find out the effect of combination of fermented Indegofera leaf and corn on the growth of Arabic chicken. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment consisted of P.1: Commercial Feed; P.2: 80% Indegofera sp leaves + 20% Corn; P.3: 70% Indegofera leaves + 30% Corn; P.4: 60% Indegofera leaves + 40% Corn. Measurement of Arab chickens weight was carried out once a week for one month. The weight data were analyzed using one-way analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indigofera contains calcium, phosphorus, potassium, xanthophyll, and carotenoids which have a major influence on egg development [9], [10]. [11] reported that indofera fermentation was able to increase the growth of Arabian chickens (Gallus turcicus). [12].…”
Section: Introductionmentioning
confidence: 99%
“…Indigofera contains calcium, phosphorus, potassium, xanthophyll, and carotenoids which have a major influence on egg development [9], [10]. [11] reported that indofera fermentation was able to increase the growth of Arabian chickens (Gallus turcicus). [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the feed ingredients that has the potential to be used as quail livestock feed is Indigofera flour, which is a local feed ingredient that is cheap, easy to obtain, available at any time and does not compete with human needs, and has nutritional qualities that can meet livestock needs. Indigofera zollingeriana is widely developed because it has quite high biomass production with good benefits as a concentrate substitute in rations [7], [8]said that indigofera fermented feed was able to increase the growth of Arabian chickens (Gallus turcicus). [9], [10] Also reported that fermented feed from indigofera was able to improve the sperm quality of Arabian chickens (Gallus turcicus).…”
Section: Introductionmentioning
confidence: 99%